Diversity and Society: Race, Ethnicity, and Gender - Joseph F. Healey (Pine Forge Press, 2007)
Derived in part from Joseph F. Healey's bestselling Race, Ethnicity, Gender, and Class, this accessible 10-chapter text teaches concepts and theories through current, engaging topics, such as the Obama election and presidency and the economic recession. An analysis of minority-dominant relations is presented clearly, reinforced through case studies and enhanced through gender and comparative perspectives. Particular emphasis is given to the history of race and ethnicity in the United States-more coverage than any other brief text. The accompanying reader includes expanded versions of the Narrative Portraits and Current Debates sections from Race, Ethnicity, Gender, and Class, as well as updated readings.